Factors associated with repetitive violent behavior of psychiatric inpatients. (February 2021) - Camus, Didier; Dan Glauser, Elise S.; Gholamrezaee, Mehdi; Gasser, Jacques; Moulin, Valerie
Highlights: In our study, a small number of psychiatric inpatients (34/4518) displays a large proportion of all violent behaviors (43%) Factors that increased the likelihood of VB occurrence were living in sheltered housing before hospitalization, suffering from schizophrenia with substance abuse comorbidity, and cumulating hospitalization days. Among situational factors, incidents in healthcare facilities were more likely to be repeated. When considering all personal, situational and institutional factors together, the interaction between length of stay and living in sheltered housing increased the risk of repetitive VB. Our results identify a small group of vulnerable patients for whom new modalities of individual care and inter-institutional networking should be developed in order to prevent the recurrence of VB. Abstract: A small number of psychiatric inpatients displays a large proportion of Violent Behaviors (VB). These can have a major impact on both victims and patients themselves. This study explored personal, situational and institutional risk factors and their combined effects, which could lead to repetitive VB (three or more assaults). Data from 4518 patients, aged 18 to 65, admitted to an acute psychiatric care facility, were included in the analysis. VB, defined as physical aggressions against another person, were assessed by the Staff Observation Aggression Scale-Revised. 414 VB were reported during the study period, involving 199 patients. 0.75 % of all patients were repetitively violent and committed 43% of all VB. Factors that were linked to repetitive VB were living in sheltered housing before hospitalization, suffering from schizophrenia with substance abuse comorbidity, cumulating hospitalization days and some situational factors, like the fact of being in nursing offices and pharmacies. When all personal, situational and institutional factors were considered together, the combined effects of length of stay and living in sheltered housing increased the risk of repetitive VB. We have identified a small group of vulnerable patients for whom new modalities of inter-institutional networking should be developed to prevent repetitive VB.